Physicochemical, Sensory, and Shelf-Life Properties of Tapioca Crispy Crackers Enriched with Fairy Mushroom (Pleurotus sajor-caju). - OUMAREE, KANITTA; SAMUTSRI, WISUTTHANA; THIMTHUAD, SUJITTRA (Current Research in Nutrition & Food Science, 2025)
To address the current oversupply and price decline of mushrooms, their nutritional and functional attributes were utilized to develop a value-added product from fairy mushrooms using simple and low-cost technology. The objective of this study was to investigate the possibility of using fairy mushrooms (Pleurotus sajor-caju (Fr. Singers)) to produce crispy tapioca crackers. This study incorporated ground fairy mushrooms at varying amounts (20%, 30%, 40%, and 50%) to replace tapioca flour in a formula for crispy tapioca crackers. Moisture content, Water activity (aw), and color of uncooked tapioca crispy crackers samples were measured. Physical characteristics (expansion, hardness, fracturability, and color) and sensory quality of the developed tapioca crispy crackers were examined using a 7-points hedonic scale by 30 semi-trained panalists. Results showed the tapioca crispy crackers with fairy mushrooms were found to be significantly darker, with less expansion, greater hardness and fracturability, and higher consumer acceptance compared to the control samples (p < 0.05). Panelists favored the 250 g substitution for its umami flavor and balanced crispiness. The tapioca crispy crackers with 250 g of fairy mushrooms obtained the highest liking scores of sensory evaluations and were chosen for the final product study. Analysis of the shelf life of the product stored in thick polypropylene bags at a room temperature of 30 °C was carried out once a week for four weeks. Moisture content, aw, Peroxide values, and lipid oxidation (TBARS) increased while the hardness and fracturability of the final tapioca crispy crackers product decreased with increasing storage time. Peroxide values remained below 0.12 g/100g, indicating acceptable oxidative stability. The tapioca crispy crackers containing 250 g of fairy mushrooms exhibited good physical and chemical properties, remaining suitable for consumption for up to four weeks. It offers a nutrient-dense, shelf-stable alternative for commercial snack production, addressing both market demand and mushroom utilization.